2018
DOI: 10.11005/jbm.2018.25.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sarcopenia, Sarcopenic Obesity, and Chronic Disease in Korean Elderly

Abstract: BackgroundIt is a very important social issue for Korea to have a healthy old age as an aged society. Aging causes a lot of physical changes, especially sarcopenia. Sarcopenia is defined as a persistent decrease in skeletal muscle and muscle strength. Sarcopenic obesity is a phenomenon in which fat is replaced instead of muscle. The purpose of this study was to examine the prevalence of sarcopenia and sarcopenic obesity in Korean elderly and to analyze the relationship with chronic disease.MethodsData from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 17 publications
2
54
0
4
Order By: Relevance
“…Several studies have reported a close correlation between SO and dyslipidemia. One study from Korea showed that the ORs of dyslipidemia increased by 1.12 and 1.50 in the sarcopenia and SO groups, respectively, compared with the values of a nonsarcopenia group [38]. Another study that included 1231 men aged > 70 years reported that serum triglyceride levels were higher in patients with SO than in those with pure sarcopenia and nonsarcopenic nonobesity [39].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a close correlation between SO and dyslipidemia. One study from Korea showed that the ORs of dyslipidemia increased by 1.12 and 1.50 in the sarcopenia and SO groups, respectively, compared with the values of a nonsarcopenia group [38]. Another study that included 1231 men aged > 70 years reported that serum triglyceride levels were higher in patients with SO than in those with pure sarcopenia and nonsarcopenic nonobesity [39].…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic pathways involved in sarcopenia and sarcopenic obesity are poorly understood. However, available scientific evidences support the role of inflammation on the process of sarcopenia, which seem to be mediated through alterations on glucose metabolism such as hyperglycaemia and insulin resistance . Insulin resistance often occurs with abdominal obesity, and the association between both conditions is influenced by an overproduction of inflammatory cytokines .…”
Section: Discussionmentioning
confidence: 99%
“…However, available scientific evidences support the role of inflammation on the process of sarcopenia, which seem to be mediated through alterations on glucose metabolism such as hyperglycaemia and insulin resistance. 8,41 Insulin resistance often occurs with abdominal obesity, and the association between both conditions is influenced by an overproduction of inflammatory cytokines. 42,43 Hyperglycaemia, insulin resistance, and excess cytokine production have been shown to impact sarcopenia by promoting the deterioration of skeletal muscle fibre diameter and protein content, as well as prompting metabolic breakdown of skeletal muscle encouraging sarcopenic process.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia was defined as less than one SD below the mean of the sex‐specific SMI value for a young reference group (aged 18‐40 years) according to methods from previous studies on Korean populations 34‐36 . The cut‐off points for sarcopenia were 30.0% in men and 26.8% in women.…”
Section: Methodsmentioning
confidence: 99%